PEMIKIRAN HUKUM ISLAM PADA MASA TABI’IN DAN TABI’UT TABI’IN SERTA MASA TAQLID - Nurlina, Nurlina; Sultan, Lomba; Hilal, Fatmawati (al-Rasῑkh: Jurnal Hukum Islam, 2024)
Islamic legal thought during the Tabi’in and Tabi’ut Tabi’in periods and the Taqlid period showed rapid and complex development. This research uses library research methods with a qualitative approach. During the Tabi’ut Tabi’in period, the development of Islamic law continued with the emergence of different schools of thought. The Taqlid period, which began after the Tabi’ut Tabi’in period, was marked by the use of Islamic law that had been previously developed by the ulama.  This research found that Islamic legal thought during the Tabi’in, Tabi’ut Tabi’in, and Taqlid periods had various methods and approaches used in interpreting the verses of the Qur'an and the hadiths of the Prophet Muhammad. The results of this research can help increase insight and knowledge about the development of Islamic law as well as the ability to understand various methods and approaches in interpreting the verses of the Koran and the hadiths of the Prophet Muhammad.